Income Satisfaction Inequality and its Causes - Ada Ferrer-i-Carbonell; Bernard M. S. van Praag (Institute for the Study of Labor (IZA), 2003)
In this paper, the concept of Income Satisfaction Inequality is operationalized on the basis of individual responses to an Income Satisfaction question posed in the German Socio-Economic Panel (GSOEP). Income satisfaction is the subjective analogue of the objective income concept and includes objective income inequality as a special case. The paper introduces a method to decompose Income Satisfaction Inequality according to the contributions from variables such as income, education, and the number of children. Given the panel structure of the data, inequality may be attributed partly to permanent individual circumstances and partly to transitory changes. The paper shows that by far the largest part of the satisfaction inequality has to be ascribed to unobserved heterogeneity. Distinguishing between a structural and an unexplained part of inequality we find that income explains the largest part of structural Income Satisfaction Inequality together with household membership; for non-working individuals, the age distribution is very relevant as well.
Keywords: I32; D63; 330; equivalent income; financial satisfaction; income satisfaction; income inequality; variance decomposition; Einkommensverteilung; Lebensqualität; Varianzanalyse; Schätzung; Schätzung; Deutschland